2013
DOI: 10.1017/s1751731113000098
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of lameness in sows using gait, footprints, postural behaviour and foot lesion analysis

Abstract: Lameness in sows has an economic impact on pig production and is a major welfare concern. The aim of the present project was to develop methods to evaluate and quantify lameness in breeding sows. Five methods to study lameness were compared between themselves and with visual gait scoring used as a reference: footprint analysis, kinematics, accelerometers, lying-tostanding transition and foot lesion observation. Fifty sows of various parities and stages of gestation were selected using visual gait scoring and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
76
2
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(91 citation statements)
references
References 28 publications
(46 reference statements)
11
76
2
2
Order By: Relevance
“…during feeding) can indicate a lame animal that is transferring weight from a weak leg to another leg (Grégoire et al, 2013). However, no associations were observed in the present study between stepping and gait-score categories, but this may be related to the data collection method.…”
Section: Discussioncontrasting
confidence: 81%
See 3 more Smart Citations
“…during feeding) can indicate a lame animal that is transferring weight from a weak leg to another leg (Grégoire et al, 2013). However, no associations were observed in the present study between stepping and gait-score categories, but this may be related to the data collection method.…”
Section: Discussioncontrasting
confidence: 81%
“…Comparison of lameness measures and associations with housing, stage of gestation and parity Using automated methods such as kinematics, Grégoire et al (2013) demonstrated that lame animals had reduced stride length and walking speed compared with sound animals. It was suggested that this reduction in speed and stride length was a way to reduce pain by decreasing the load on the affected leg.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The occurrence and severity of lameness can be determined by several methods such as visual inspection of the gait (Main et al, 2000;Nalon et al, 2014) and using kinematic techniques like pressure mats and accelerometers (Grégoire et al, 2013;Pluym et al, 2013b;Meijer et al, 2014). However, none of these methods directly evaluates the effects of lameness on the capability of locomotion.…”
Section: Introductionmentioning
confidence: 99%